The effect of auxiliary exercises to develop the speed of the kinematic response of volleyball players from a seated position - Subhan Sakhi, Ali; Haydar Dawood, Hassan; QaisAkramSabaa (International Journal of Psychosocial Rehabilitation, 2020)
The first chapter included the introduction to the research and its importance, and the researchers dealt with the advantages of the game of volleyball from the sitting position, which has specific features that distinguish it from other group games. As for the research problem, it crystallized in the team players ’lack of modern sports equipment, so the researchers decided to prepare exercises using optical devices and rubber ropes to develop the speed of movement response and help players to perform their technical skills with the utmost speed and accuracy. As for the objectives of the research, they were: 1. Preparing exercises with assistive means to develop the speed of movement response for volleyball players—sitting. 2. Identify the effect of exercises with assistive means to develop the speed of the kinematic response of volleyball players—seating. As for the hypotheses for research, they were: 1. There are statistically significant differences between the results of the pre- and post-tests for the experimental group and in favor of the post-test. 2: Exercise has an effect on developing the response speed of volleyball players from the sitting position. The second chapter included a detail in the research methodology and field procedures, as the researchers used the experimental method in the style of one experimental group with two pre- and post-tests, and the research sample was chosen by the deliberate method, and they are the players of the national volleyball team from the sitting position of 14 players. As for the third chapter, the statistical results extracted were presented in graphical tables with the analysis and discussion of those results in accordance with the theoretical knowledge foundations assigned by the scientific references. In light of the experiment carried out by the researchers and the results achieved through tests and statistical means, they reached conclusions, which are: 1. The different and varied motor response speed exercises using auxiliary tools helped to develop the motor response speed of volleyball players from the sitting position. 2. The use of auxiliary tools in the exercises increased the players’ experience in reducing the response time and thus the speed of decision-making. All this improved the level of performance of the players. 3. The use of multiple stimuli in one exercise exposes the player’s movement programs to difficult requirements (which are somewhat similar to the playing conditions) and with regular repetitions, which adjusts the player to those stimuli and increases experience, and then reduces the time of the movement’s response to him. As for the recommendations, they were: 1. The use of modern devices and tools in training for volleyball players from a sitting position because of their importance in developing the speed of the motor response. 2. Relying on advanced and modern equipment when building tests because they reflect the true level of individuals, far from bias. 3. Paying attention to exercises to develop the speed of the kinetic response using multiple and various stimuli and resistances, provided that the performance is from movement (i.e., linking more than one movement in a single exercise). 4. Giving the player complex or multiple stimuli to make the exercises similar to the real playing conditions, especially in games that require speed and accuracy at the same time.